FRI0077 The Use of Ultrasound to Detect Residual Joint Inflammation in Patients with Rheumatoid Arthritis in Clinical Disease Remission. (9th June 2015) - Kaeley, G.S.; Nishio, M.J.; Goyal, J.R.; MacCarter, D.K.; Wells, A.F.; Cardoso, A.; Liu, S.; Kalabic, J.; Kupper, H.
Abstract : Background: Patients (pts) with rheumatoid arthritis (RA), who achieve clinical disease remission by treatment with disease-modifying agents may have residual joint inflammation and vascularization, which can be detected by Power Doppler (PD) ultrasonography. The aim of this analysis was to evaluate the proportion of RA pts with PD activity, 24 weeks (wks) after the addition of adalimumab (ADA) to methotrexate (MTX). Methods: MUSICA (NCT01185288 ), a 24 wk double-blind, randomized, controlled trial evaluated the efficacy of 2 different dosages of MTX (7.5 or 20 mg/wk) plus ADA (40 mg every other wk) in RA pts with inadequate response to MTX. For this analysis, the MTX dosage groups were combined. Synovial vascularization was assessed by PD US at 10 joints (bilateral dorsal and volar views of metacarpophalangeal joints 2, 3, 5; dorsal images alone of metatarsophalangeal joint 5 and wrists), at baseline (BL), wks 4, 8, 12, 16, 20 and 24. Images were scored by ultrasound-experienced rheumatologists using a semi-quantitative 4-grade scale. Joint swelling was assessed for the same 10 joints (SJC10). Disease activity was assessed by 28-joint count disease activity score using C-reactive protein (DAS28[CRP]) (remission <2.6, LDA <3.2, MDA 3.2- <5.1, HDA ≥5.1), and simplified disease activity index (SDAI) (remission ≤3.3, LDA ≤11, MDA 11-≤26, HDA >26). Pearson's coefficient (ρ) was used to assess correlation between continuous variables. Results: After 24 wks of treatment with ADA +MTX, 44/309 pts (14%) were in DAS28(CRP) remission (mean PD score, 3.3); 18/309 (5.8%) pts were in SDAI remission (mean PD score, 2.7). At wk 24, for the 10 joints selected, 30/44 (68%) of pts in DAS28(CRP) remission had positive PD scores, while only 15 pts (34%) had ≥1 swollen joint, and only 6 pts (13.6%) had ≥1 tender joint. Ten out of 18 (55%) pts in SDAI remission had a positive PD score, while none had swollen/tender joints. A poor correlation (ρ<0.2) was observed between PD scores and clinical disease scores such as DAS28, SJC66, SJC28, TJC68, TJC28, CDAI, SDAI, PhGA, PGA-pain and disease duration. There was poor correlation (ρ=0.184) between the change from BL to wk 24 in PD scores, and the change from BL to wk 24 in DAS28(CRP) or SDAI. The corresponding shifts in disease activity, mean PD score and SJC10 scores are presented (Table ). Conclusions: In agreement with other studies, residual joint inflammation was detected by PD US in pts in clinical remission; therefore ultrasound can offer additional information to that obtained from clinical disease measures. Acknowledgements: AbbVie sponsored the study (NCT01185288 ), contributed to its design, participated in the collection, analysis, and interpretation of the data, and in the writing, reviewing, and approval of the final version. Medical writing support was provided by Naina Barretto, Ph.D., of AbbVie. Disclosure of Interest: G. Kaeley Consultant for: AbbVie, M. Nishio Speakers bureau: AbbVie, J. Goyal Consultant for: AbbVie, D. MacCarter Consultant for: AbbVie, Speakers bureau: AbbVie, A. Wells Consultant for: AbbVie, A. Cardoso Employee of: AbbVie, S. Liu Employee of: AbbVie, J. Kalabic Employee of: AbbVie, H. Kupper Employee of: AbbVie